Occurrence, Distribution and Dynamics of Perchlorate in Soil, Water, Fertilizers, Vegetables and Fruits and Associated Human Exposure in Chile - Arancibia-Miranda, N; Arancibia-Miranda, N (Springer Science and Business Media B.V., 2022)
Perchlorate (ClO4−) has been identified as a persistent environmental contaminant of concern. Perchlorate exposure is a potential health concern because it interferes with hormone production by thyroid gland. Food (fruits and vegetables) and drinking water are an important source of human exposure to perchlorate. However, little is known about the occurrence of perchlorate in Chile. The purpose of this study was to determine the occurrence of perchlorate in 145 samples (soil, drinking water, surface water, groundwater, fertilizers, fruits and vegetables) collected across Chile and estimate associated exposure to consumers. Our results show that perchlorate was detected in soil (median: 22.2 ng g−1), drinking water (median: 3.0 ng mL−1), fruits (median: 0.91 ng g−1 fresh weight [FW]), lettuce (median: 5.0 ng g−1 FW) and chard (median: 4.15 ng g−1 FW). Interestingly, perchlorate concentrations detected in drinking water from three regions (Serena, Copiapo and Illapel) exceeded the USEPA interim drinking water health advisory level of 15 ng mL−1. Median concentrations of perchlorate in non-nitrogenous fertilizers (3.1 mg kg−1) were higher than those in nitrogenous fertilizers (1.3 mg kg−1). Estimated daily intake (EDI) of perchlorate via drinking water was lower than the USEPA’s reference dose (7000 ng kg−1 bw day−1). The EDI of perchlorate via vegetables (chard and lettuce) produced in northern Chile was three times higher than those produced in other regions. The results of this study provide information about perchlorate sources in Chile, which will be helpful in modifying current regulations. © 2020, Springer Nature B.V.